Ontogeneza cirkadianega ritma dejavnosti in počivanja ter ritma izločanja melatonina pri dojenčkih z navideznim življenje ogrožajočim dogodkom (NŽOD) - Mlekuš, Katarina (Medicinski razgledi, 2008)
Background: So far the ontogenesis of the rest-activity rhythm and melatonin excretion rhythm in infants have been treated separately and no direct correlation between them in the first six months of life has been defined. In infants with apparent life threatening event (ALTE) the delayed ontogenesis ofmelatonin excretion rhythm has been proved, whereas the ontogenesis of rest-activity rhythm has been defined to be identical to that of healthy infants. AIM: The aim of this study is to find out if any correlation between the rest-activity rhythm and melatonin excretion rhythm in the first six months of life exists and to test if the ontogenesis of the two rhythms in infants with ALTE differs from that of healthy infants. Subjects and methods: The study involved 42 infants who were admitted to the Department of Child, Adolescent & Developmental Neurology of the University Children's Hospital in Ljubljana due to the apparent life threatening event (ALTE). The average age of the infants at the time of the event was from 0 to 28 weeks (average 8.6 +-5.5). After the first evaluation they were followed-up at 3, 4.5 and 6 months. In addition, 24-hour actigraphic recording of infants' body movements was made regularly and urine was collected in 4-hour intervals to measure melatonin's main degradation product in urine 6- sulphatoxymelatonin (6SMT). The data was analysed bygeneral linear model, the Tukey-Kramer post-hoc tests,the Wilcoxson signed rank test, the Friedman two-way ANOVA and the Spearman's correlation coefficient. Results: No correlation was found in any of the age groups between the speed of excretion of 6SMT and the average indexof activity (the Spearman's correlation coefficient: r5 = -0.088 and p = 0.483 at one month, ry = 0.070 and p = 0.543 at two months, rs = -0.092 and p = 0.562 at three months, rs = -0.147 and p = 0.437 at four-and-a-half months, rs = -0.148 and p = 0.139 at six months). (Abstract truncated at 2000 characters)
Keywords: Melatonin; Sudden Infant Death; Secretion; Budnost; Circadian Rhythm; Dnevni ritem; Sleep; Spanje; Wakefulness; Nenadna smrt dojenčka; baby; Infant; Dojenček; cirkadiani ritem; dojenčki